Impact of small and medium enterprises in generating new jobs in case of Kosovo: Array - Gashi, Rrezarta (Journal of Danubian Studies and Research, 2022)
This study is an original study and adds to the research debate on the impact of small and medium enterprises in generating new jobs, with a special focus on the industry and services sector, as in Kosovo for these sectors still do not there has been special research. The objective of this research paper is presents the impacts of small and medium enterprises have in generating new jobs. To achieve the stated objective and to prove the hypotheses in this research, the OLS regression model has been used whereas the data processing has been done through SPSS. This research paper has been conducted by using secondary data collected by the World Bank and Kosovo Agency of Statistics, for the time period 2012-2018. Results in this research paper from this model show that the industry and services sector affects generating new jobs in Kosovo, therefore there is a positive correlation between the presented variables. Also we can notice a positive correlation between the GDP and employment rate. The results presented in this research paper can be used as a guide for new businesses in the services and industry sector and their impact on the generation of new jobs in Kosovo, as well as efforts to further improve performance in these sectors.